Homeownership motivation, rationality, and housing prices: Evidence from gloom, boom, and bust‐and‐boom economies - Alexiou, Constantinos; Chan, Aaron‐Samuel; Vogiazas, Sofoklis (Wiley, 2018)
By focusing on three types of homebuyers, we address three questions: (a) Do households drive housing prices? (b) Do households and landlords act rationally in their buying decisions? (c) Is the market conducive to promoting homeownership or is it a speculators' territory? We use system Generalized Method of Moments (GMM) estimations based on 1970–2016 data, for 34 economies clustered as gloom, boom, or bust‐and‐boom, and we provide novel evidence that all three types of homebuyers contribute significantly to the determination of housing prices. Households and landlords seem to act irrationally as their decisions are not greatly affected by housing affordability or shrinking yields.
Keywords: Housing prices; Homeowners; Speculation; GMM